2020
DOI: 10.3390/antiox9090866
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoporotic Effects of Antioxidant Peptides PIISVYWK and FSVVPSPK from Mytilus edulis on Ovariectomized Mice

Abstract: Numerous amounts of evidence suggest that bioactive peptides with diverse physiological activities can be nutraceuticals or potential drug candidates. In this study, blue mussel-derived antioxidant peptides PIISVYWK and FSVVPSPK were subjected to evaluate their osteogenic effect in mouse bone marrow mesenchymal stem cells (mBMMSCs) followed by an in vivo anti-osteoporotic effect. Treatment of PIISVYWK and FSVVPSPK on mBMMSCs stimulated alkaline phosphatase activity and calcification. Western blot results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Apoptosis of osteoblasts and osteocytes with decreased osteoblast count can be induced by oxidative stress due to the activation of nuclear transcription factor kB (NF-kB) and extracellular signal-regulated kinases (ERK) signaling pathways [ 25 ], which represses the bone formation rate via Wnt/β-catenin signaling pathways in osteoblastogenesis [ 26 ]. ROS is involved in bone resorption through direct bone degradation by osteoclast-generated superoxide or through enhancement of osteoclast differentiation and function [ 22 , 23 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Osteoporosismentioning
confidence: 99%
“…Apoptosis of osteoblasts and osteocytes with decreased osteoblast count can be induced by oxidative stress due to the activation of nuclear transcription factor kB (NF-kB) and extracellular signal-regulated kinases (ERK) signaling pathways [ 25 ], which represses the bone formation rate via Wnt/β-catenin signaling pathways in osteoblastogenesis [ 26 ]. ROS is involved in bone resorption through direct bone degradation by osteoclast-generated superoxide or through enhancement of osteoclast differentiation and function [ 22 , 23 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Osteoporosismentioning
confidence: 99%
“…To date, many BAPs have been isolated and identified from marine dietary protein hydrolysates [27]. In addition, previous studies have identified specific BAPs in blue mussel protein hydrolysates that have been attributed antioxidant, antithrombotic, antihypertensive, osteogenic, and anti-osteoporotic effects [19,20,[28][29][30][31]. Blue mussel protein hydrolysate produced by α-chymotrypsin has been previously identified as a potential cytoprotective agent [1].…”
Section: Discussionmentioning
confidence: 99%
“…45 Previous research has shown that mussel peptides, ginsenosides Rg3, and Palmul-tang (an herbal remedy) could decrease osteoporosis by activating the BMP-2 pathway and promoting the expression of critical factors in osteoblasts. [46][47][48] In this study, the effect of P-GM-1 on the expression of BMP-2 and other important bone transcription factors in OVX-mice was further determined. The results are shown in Fig.…”
Section: Papermentioning
confidence: 99%